CRIMINAL LIABILITY FOR PERPETRATORS THREATENING THE SPREAD OF IMMORAL VIDEOS ON SOCIAL MEDIA - Ismail Koto; Ramlan Ramlan; Tengku Erwin Syahbana; Rachmad Abduh; Ibrahim Nainggolan (JHR (Jurnal Hukum Replik), 2023)
The rapid development of information and communication technology has affected human development throughout the world. Technological advances in the digitalization era have been made by humans to facilitate human activities such as accessing information and knowledge so that humans can do many things in a short time. Cases of immoral crimes almost always occur in Indonesia and attract public attention. The level of immoral crimes in Indonesia is very high and varied. The perpetrators of immoral crimes also range from children, adults, to the elderly, even early childhood. Two components consist of immoral crimes: norms of decency and norms of decency. In order to function as a basis for providing a sense of justice and legal certainty to the people of Indonesia, the norms of decency play a very important role. This research is normative legal research, namely legal research that places law as a building system of norms. Pornographic crimes that occurred in the Republic of Indonesia are clearly contrary to the principles held by Indonesian society. Pornography crimes often cause concern for the community. The Electronic Information and Transaction Law is a provision that applies to anyone who commits legal acts whether within the scope of Indonesian jurisdiction and/or outside Indonesian territory and causing harm to Indonesia's interests